2004
DOI: 10.1080/08035250410032926
|View full text |Cite
|
Sign up to set email alerts
|

Re-hospitalization in infants younger than 29 weeks' gestation in the EPIPAGE cohort

Abstract: Infants born before 29 wk have a very high risk of re-hospitalization. The associated factors can help define high-risk groups at discharge from the neonatal unit who need special surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…The rehospitalization rate for patients enrolled in this trial was 43.4% in the first year of life and 57.8% during the 4.5 year follow-up, which is consistent with other studies with similar enrollment criteria [17, 19, 20, 22, 23]. The finding that almost 30% of subjects required multiple hospital readmissions, averaging 3.9 admissions over the study period, is remarkable and demonstrates a high degree of morbidity in these infants.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The rehospitalization rate for patients enrolled in this trial was 43.4% in the first year of life and 57.8% during the 4.5 year follow-up, which is consistent with other studies with similar enrollment criteria [17, 19, 20, 22, 23]. The finding that almost 30% of subjects required multiple hospital readmissions, averaging 3.9 admissions over the study period, is remarkable and demonstrates a high degree of morbidity in these infants.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that almost 30% of subjects required multiple hospital readmissions, averaging 3.9 admissions over the study period, is remarkable and demonstrates a high degree of morbidity in these infants. The risk factors for hospital readmission that have been previously identified [8, 17, 19, 20] are similar to those we identified for readmission to the ICU. One notable difference is the lack of CLD as a risk factor for either hospital or ICU readmission in our study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The EPIPAGE study demonstrated that preterm infants discharged with lower weight and postmenstrual age did not have higher rates of re-hospitalization, and that the number of re-admissions was not correlated with the initial LOS [11]. It seems conceivable that LOS can be influenced by the age in which the newborn leaves the incubator.…”
Section: Discussionmentioning
confidence: 99%